(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate changes in serum glucose and HbA1c concentrations after 3 months of treatment in newly diagnosed type 2 diabetes mellitus (T2DM) patients at Tho Xuan General Hospital, Thanh Hoa, in 2025. Subjects and Methods: A cross-sectional analytical study combined with longitudinal follow-up was conducted on 137 patients diagnosed with T2DM for the first time at Tho Xuan General Hospital from January 2025 to June 2025. Results: The study on 137 newly diagnosed T2DM patients showed that after 3 months, metabolic indices improved with statistical significance (p<0.001). In the inpatient group, glucose levels decreased from 10.4 ± 4.1 to 8.3 ±2.0 mmol/L; HbA1c decreased from 9.1 ± 1.9% to 8.2 ±1.3%. In the outpatient group, glucose levels decreased from 6.6 ±1.4 to 6.3 ± 0.8 mmol/L. The rate of achieving dual targets (glucose 4.4–7.2 mmol/L and HbA1c <7.0%) was 16.1%. The correlation between glucose and HbA1c became stronger post-treatment (r increased from 0.496 to 0.624). Data dispersion (IQR, SD) narrowed significantly, reflecting reduced glycemic variability. Concurrently, the lipid profile showed positive changes, with total cholesterol decreasing from 5.78 ± 0.78 to 5.09 ± 0.70 mmol/L and LDL-C decreasing from 3.34 ± 0.61 to 2.69 ± 0.62 mmol/L (p<0.05). Conclusion: Intensive treatment during the first 3 months significantly improved glycemic indices and lipid profiles. However, the rate of achieving HbA1c targets remains low, necessitating individualized treatment strategies and enhanced adherence monitoring from the initiation phase.